TEM investigations on the nanoheteroepitaxy of semiconductors - Lindner, Jörg

Microscopic studies of plasmonic nanostructures II - Lindner, Jörg

Nanostrukturierte Oberflächen, nicht nur zum Spass - Lindner, Jörg

Integrating Service Matchers into a Service Market Architecture - Platenius, Marie Christin; Becker, Steffen; Schäfer, Wilhelm (Proceedings of the 8th European Conference on Software Architecture (ECSA 2014))
Service markets provide software components in the formof services. In order to enable a service discovery that satisfies servicerequesters and providers best, markets need automatic service matching:approaches for comparing whether a provided service satisfies a servicerequest. Current markets, e.g., app markets, are limited to basic keywordbasedsearch although many better suitable matching approaches aredescribed in literature. However, necessary architectural decisions forthe integration of matchers have a huge impact on quality propertieslike performance or security.Architectural decisions wrt. servicematchers have rarely been discussed,yet, and systematic approaches for their integration into service marketsare missing. In this paper, we present a systematic integration approachincluding the definition of requirements and a discussion on architecturaltactics. As a benefit, the decision-making process of integrating servicematchers is supported and the overall market success can be improved.

RSDL workbench results for OAEI 2014 - Schwichtenberg, Simon; Gerth, Christian; Engels, Gregor (Proceedings of the 9th International Workshop on Ontology Matching collocated with the 13th International Semantic Web Conference (ISWC 2014), Riva del Garda, Trentino, Italy, October 20, 2014.)

Incorporating Reputation Information into Decision-Making Processes in Markets of Composed Services - Jungmann, Alexander; Brangewitz, Sonja; Petrlic, Ronald; Platenius, Marie Christin (International Journal On Advances in Intelligent Systems (IntSys))
One goal of service-oriented computing is to realize future markets of composed services. In such markets, service providers offer services that can be ﬂexibly combined with each other. However, although crucial for decision-making, market participants are usually not able to individually estimate the quality of traded services in advance. To overcome this problem, we present a conceptual design for a reputation system that collects and processes user feedback on transactions, and provides this information as a signal for quality to participants in the market. Based on our proposed concept, we describe the incorporation of reputation information into distinct decision-making processes that are crucial in such service markets. In this context, we present a fuzzy service matching approach that takes reputation information into account. Furthermore, we introduce an adaptive service composition approach, and investigate the impact of exchanging immediate user feedback by reputation information. Last but not least, we describe the importance of reputation information for economic decisions of different market participants. The overall output of this paper is a comprehensive view on managing and exploiting reputation information in markets of composed services using the example of On-The-Fly Computing.

Improving Service Specifications for the Service Matching on a Service Market - Taherinajafabadi, Vahide

HSkip+: A Self-Stabilizing Overlay Network for Nodes with Heterogeneous Bandwidths - Feldotto, Matthias; Scheideler, Christian; Graffi, Kalman (Proceedings of the 14th IEEE International Conference on Peer-to-Peer Computing (P2P))
In this paper we present and analyze HSkip+, a self-stabilizing overlay network for nodes with arbitrary heterogeneous bandwidths. HSkip+ has the same topology as the Skip+ graph proposed by Jacob et al. [PODC 2009] but its self-stabilization mechanism significantly outperforms the self-stabilization mechanism proposed for Skip+. Also, the nodes are now ordered according to their bandwidths and not according to their identifiers. Various other solutions have already been proposed for overlay networks with heterogeneous bandwidths, but they are not self-stabilizing. In addition to HSkip+ being self-stabilizing, its performance is on par with the best previous bounds on the time and work for joining or leaving a network of peers of logarithmic diameter and degree and arbitrary bandwidths. Also, the dilation and congestion for routing messages is on par with the best previous bounds for such networks, so that HSkip+ combines the advantages of both worlds. Our theoretical investigations are backed by simulations demonstrating that HSkip+ is indeed performing much better than Skip+ and working correctly under high churn rates.

Horizontale Fusionen: Theorie und Praxis am Beispiel zweier Entscheidungen des Bundeskartellamtes - Eusterholz, Fabian

Hiding software components using functional encryption - Jochheim, Janek

Handling Incomplete Service Specifications using Fuzzy Matching - Vijapurwala, Shafi

Group Signature Schemes with Strong Exculpability - Bemmann, Pascal

Grammar-based model transformations - Besova, Galina; Steenke, Dominik; Wehrheim, Heike (Proceedings 3rd Workshop on Model Driven Approaches in System Development (MDASD))
Model transformation is a key concept in modeldrivensoftware engineering. The definition of model transformationsis usually based on meta-models describing the abstractsyntax of languages. While meta-models are thereby able to abstractfrom superfluous details of concrete syntax, they often loosestructural information inherent in languages, like information onmodel elements always occurring together in particular shapes.As a consequence, model transformations cannot naturally re-uselanguage structures, thus leading to unnecessary complexity intheir development as well as analysis.In this paper, we propose a new approach to model transformationdevelopment which allows to simplify and improve thequality of the developed transformations via the exploitation ofthe languages’ structures. The approach is based on context-freegrammars and transformations defined by pairing productions ofsource and target grammars. We show that such transformationsexhibit three important characteristics: they are sound, completeand deterministic.

Generierung von Eigenschaftsprüfern in einem Hardware/Software-Co-Verifikationsverfahren - Pauck, Felix

Gender and ethnic discrimination in hiring : evidence from field experiments in the German labor market - Kolle, Andre
The present thesis investigates the prevalence of and the reasons for hiring discrimination against women and ethnic Turks in the German labor market. Subsequent to a discussion of how to reveal discrimination, the literature on wage and employment differences inside and outside the German labor market is reviewed. Afterwards, different (economic) theories explaining inequalities in labor markets are presented. In the empirical analyses a field experiment - the so called correspondence testing - is conducted where matched pairs of (fictitious) male and female as well as German-named and Turkish-named applicants respond to, respectively, 656 and 608 (real) apprenticeship offers in predominantly male-dominated jobs. Descriptive results and econometric analyses using probit regressions on various model specifications indicate that the female applicant has a 19 percent lower callback probability compared to her male counterpart. However, differential treatment is both job- and firm-type driven. While callback rates are not statistically different from zero in female-dominated and “gender-neutral” occupations, they prevail in jobs where men are overrepresented. Furthermore, discrimination is restricted to late recruiters, i.e., companies that advertise their vacancies right before the apprenticeship is supposed to start. Similar conclusions can be drawn from the study investigating ethnic discrimination. The 32 percent lower callback probability of the Turkish-named applicant decreases if early rather than late recruiters are addressed. Apart from that, comparing response and callback rates to the candidates using different experimental designs, i.e., sending out single versus pairs of applications, yields no statistically significant differences demonstrating the unbiasedness of the correspondence approach.

Fuzzy Matching of Service Price Specifications - Merschjohann, Sven

Fujisaki-Okamoto Transformation - Lippert, Jan

Formal Semantics of Probabilistic SMT Solving in Verification of Service Compositions - Sanati, Maryam

Finding Optimal Self-Adaption Rules by Design-Space Exploration - Jojiju, Suman

Fast and Flexible Automatic Composition of Semantic Web Services - Finkensiep, Christoph

Evaluation of Color Spaces for Robust Image Segmentation - Jungmann, Alexander; Jatzkowski, Jan; Kleinjohann, Bernd (Proceedings of the 9th International Conference on Computer Vision Theory and Applications (VISAPP))
In this paper, we evaluate the robustness of our color-based segmentation approach in combination with different color spaces, namely RGB, L*a*b*, HSV, and log-chromaticity (LCCS). For this purpose, we describe our deterministic segmentation algorithm including its gradually transformation of pixel-precise image data into a less error-prone and therefore more robust statistical representation in terms of moments. To investigate the robustness of a specific segmentation setting, we introduce our evaluation framework that directly works on the statistical representation. It is based on two different types of robustness measures, namely relative and absolute robustness. While relative robustness measures stability of segmentation results over time, absolute robustness measures stability regarding varying illumination by comparing results with ground truth data. The significance of these robustness measures is shown by evaluating our segmentation approach with different color spaces. For the evaluation process, an artificial scene was chosen as representative for application scenarios based on artificial landmarks.

Evaluation of a Hybrid Packet-/Circuit-Switched Data Center Network - Dornseifer, Veit

Evaluating the Influence of Different Abstraction Levels of Software Design on Performance prediction - Bulk, Benjamin

Estimating Functional Reusability of Services - Mohr, Felix (Proceedings of the 12th International Conference on Service Oriented Computing (ICSOC))
Services are self-contained software components that can be used platform independent and that aim at maximizing software reuse. A basic concern in service oriented architectures is to measure the reusability of services. One of the most important qualities is the functional reusability, which indicates how relevant the task is that a service solves. Current metrics for functional reusability of software, however, either require source code analysis or have very little explanatory power. This paper gives a formally described vision statement for the estimation of functional reusability of services and sketches an exemplary reusability metric that is based on the service descriptions.

Entwicklung eines mathematischen Modells zur Optimierung der Struktur eines Trinkwasserbehälters - Herbort, Maik

Entwicklung eines Konzepts zur Kodierung eines objektorientierten Typsystems in SMT - Krakau, Andreas

Energy-efficient Scheduling Algorithms - Kling, Peter
In meiner Dissertation beschäftige ich mich mit dem Entwurf und der Analyse energieeffizienter Schedulingalgorithmen, insbesondere für sogenannte Speed-Scaling Modelle. Diese stellen das theoretische Pendant von Techniken wie AMDs PowerNOW! und Intels SpeedStep dar, welche es erlauben die Geschwindigkeit von Prozessoren zur Laufzeit an die derzeitigen Bedingungen anzupassen. Theoretische Untersuchungen solcher Modelle sind auf eine Arbeit von Yao, Demers und Shenker (FOCS'95) zurückzuführen. Hier kombinieren die Autoren klassisches Deadline-Scheduling mit einem Prozessor der Speed-Scaling beherrscht. Es gilt Jobs verschiedener Größe fristgerecht abzuarbeiten und die dabei verwendete Energie zu minimieren. Der Energieverbrauch des Prozessors wird durch eine konvexe Funktion $\POW\colon\R_{≥0}→\R_{≥0}$ modelliert, welche die Geschwindigkeit auf den Energieverbrauch abbildet.Meine Dissertation betrachtet verschiedene Varianten des ursprünglichen Speed-Scaling Modells. Forschungsrelevante Ergebnisse sind in den Kapiteln 3 bis 6 zu finden und erstrecken sich über die im Folgenden beschriebenen Aspekte:- Kapitel 3 und 4 betrachten verschiedene Price-Collecting Varianten des Originalproblems. Hier dürfen einzelne Deadlines verfehlt werden, sofern eine jobabhängige Strafe gezahlt wird. Ich entwerfe insbesondere Online-Algorithmen mit einer beweisbar guten Competitiveness. Dabei liefern meine Ergebnisse substantielle Verbesserungen bestehender Arbeiten und erweitern diese unter Anderem auf Szenarien mit mehreren Prozessoren.- In Kapitel 5 wird statt des klassischen Deadline-Schedulings eine Linearkombination der durchschnittlichen Antwortzeit und des Energieverbrauchs betrachtet. Die Frage, ob dieses Problem NP-schwer ist, stellt eine der zentralen Forschungsfragen in diesem Gebiet dar. Für eine relaxierte Form dieser Frage entwerfe ich einen effizienter Algorithmus und beweise seine Optimalität.- Das letzte Kapitel betrachtet ein Modell, welches – auf den ersten Blick – nicht direkt zur Speed-Scaling Literatur zählt. Hier geht es stattdessen um ein allgemeines Resource-Constrained Scheduling, in dem sich die Prozessoren zusammen eine gemeinsame, beliebig aufteilbare Ressource teilen. Ich untersuche die Komplexität des Problems und entwerfe verschiedene Approximationsalgorithmen.

Light Scattering By Random Irregular Particles With Different Morphology - Grynko, Yevgen; Zubko, Evgenij
We simulate numerically light scattering by random irregular particles of two classes of shape: Gaussian random field particles and agglomerated debri particles. Comparison of the angular dependencies of the scattering matrix elements for the case of non-absorbing material shows qualitative similarity of optical properties of both types despite different morphology of scatterers. Absorbing particles result in the difference in linear polarization. However, a strong similarty remains for the intensity curves.

Energy-Efficient Queuing with Delayed Deactivation - Bredenbals, Nico

Embedding FPGA Overlays into Configurable Systems-on-Chip: ReconOS meets ZUMA - Wiersema, Tobias; Bockhorn, Arne; Platzner, Marco (Proceedings of the International Conference on ReConFigurable Computing and FPGAs (ReConFig))
Virtual FPGAs are overlay architectures realized on top of physical FPGAs. They are proposed to enhance or abstract away from the physical FPGA for experimenting with novel architectures and design tool flows. In this paper, we present an embedding of a ZUMA-based virtual FPGA fabric into a complete configurable system-on-chip. Such an embedding is required to fully harness the potential of virtual FPGAs, in particular to give the virtual circuits access to main memory and operating system services, and to enable a concurrent operation of virtualized and non-virtualized circuitry. We discuss our extension to ZUMA and its embedding into the ReconOS operating system for hardware/software systems. Furthermore, we present an open source tool flow to synthesize configurations for the virtual FPGA.

Radio Frequency Electromechanical Control over a Surface Plasmon Polariton Coupler - Ruppert, Claudia; Förster, Frederike; Zrenner, Artur; Kinzel, Jörg B.; Wixforth, Achim; Krenner, Hubert J.; Betz, Markus (ACS Photonics)
We explore the impact of ∼500 MHz surface acoustic waves traveling across a commensurable plasmonic grating coupler. A stroboscopic technique involving surface acoustic waves synchronized to a modelocked optical source allows to time-resolve the dynamical impact of the electromechanically induced perturbation. The surface acoustic wave periodically enhances or decreases the surface ripple of the static grating. Most remarkably, the dynamic surface deformation deliberately modulates the coupler’s efficiency by ±2% during the ∼2 ns acoustic cycle.
Keywords: nanomechanics; plasmonics; surface acoustic waves; surface plasmon polaritons

Ein selbst-stabilisierender Algorithmus für das Finite Sleep Problem in Skip+ Graphen - Luo, Linghui

Efficient Computation of Optimal Energy and Fractional Weighted Flow Trade-off Schedules - Antoniadis, Antonios; Barcelo, Neal; Consuegra, Mario; Kling, Peer; Nugent, Michael; Pruhs, Kirk; Scquizzato, Michele (Proceedings of the 31st Symposium on Theoretical Aspects of Computer Science (STACS))
We give a polynomial time algorithm to compute an optimal energy and fractional weighted flow trade-off schedule for a speed-scalable processor with discrete speeds.Our algorithm uses a geometric approach that is based on structural properties obtained from a primal-dual formulation of the problem.

Easy-to-use on-the-fly binary program acceleration on many-cores - Damschen, Marvin

Die ökonomischen Auswirkungen der Kronzeugenregelung am Beispiel des Kaffeerösterkartells - Wemhöner, Vanessa

Designing an Anonymous and Secure Reputation System Using a Group Signature Variant - Kokoschka, Andreas

Decision Making under Asymmetric Information in Markets for Experience Goods: Empirical Evidence of Signaling Effects on Consumer Perceptions - Kaimann, Daniel

Vermögensteuer als Beitrag der Wohlhabenden für mehr Gleichheit - eine wirtschaftswissenschaftliche Betrachtung eines Steuerreformvorschlags - Sureth-Sloane, Caren (Wirtschaftspädagogische Handlungsfelder)

Effizienzmessung industrieller Dienstleistungen mittels Data Envelopment Analysis (ServDEA) - Backhaus, Klaus; Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Bröker, Ole; Alexander Brüne, Philipp; Dietrich, Hanns-Alexander; Knackstedt, Ralf; Peter Rauer, Hans; Reichle, Florian; Wilken, Robert (Produktivität von Dienstleistungen)

Zur Attraktivität von Advance Tax Rulings (ATRs) und Advance Pricing Agreements (APAs) für Investoren und Steuerbehörden: The Attractiveness of Advance Tax Rulings (ATRs) and Advance Pricing Agreements(APAs) for Investors and Tax Authorities - Kortebusch, Pia

Should Multinational Companies Request an Advance Pricing Agreement (APA) - Or Shouldn't They? - Kortebusch, Pia

Can Tax Rate Increases Foster Investment Under Entry and Exit Flexibility? - Insights from an Economic Experiment - Fahr, Rene; Janssen, Elmar A.; Sureth-Sloane, Caren

Do Investors Request Advance Tax Rulings to Alleviate Tax Risk (and do tax authorities provide them)? A Joint Taxpayers’ and Tax Authorities’ View on Investment Behavior - Diller, Markus; Kortebusch, Pia; Schneider, Georg; Sureth-Sloane, Caren

Boon or Bane? Advance Tax Rulings As a Measure to Mitigate Tax Uncertainty and Foster Investment - Diller, Markus; Kortebusch, Pia; Schneider, Georg; Sureth-Sloane, Caren

Gibt es eine optimale Frauenquote? - Gilroy, Bernard Michael; Heimann, Anastasia; Schopf, Mark (WiSt-Wirtschaftswissenschaftliches Studium)

Vom Wollen und Können ethischen Entscheidens - Fahr, Rene (Theologie und Glaube)

Customer satisfaction in private banking - Seiler, Volker; Rudolf, Markus (Credit and Capital Markets - Kredit und Kapital)

Verantwortungsvolles Handeln in Unternehmen. Die Rolle von kognitiven Verzerrungen und Selbsttäuschung bei ethischen Entscheidungen - Fahr, Rene

Contagious conflict: spill-over effects of labor conflict between and within organizations - Akkerman, Agnes; Torenvlied, René; Lehr, Alex; Thommes, Kirsten (Social conflict within and between groups)

Die Rechte von Arbeitnehmervertretern in Ost- und Westeuropa - Einheitseuropa oder Zweiklassengesellschaft? - Thommes, Kirsten; Walgenbach, Peter; Oertel, Simon

FlowDroid: Precise Context, Flow, Field, Object-sensitive and Lifecycle-aware Taint Analysis for Android Apps - Arzt, Steven; Rasthofer, Siegfried; Fritz, Christian; Bodden, Eric; Bartel, Alexandre; Klein, Jacques; Le Traon, Yves; Octeau, Damien; McDaniel, Patrick (Proceedings of the 35th ACM SIGPLAN Conference on Programming Language Design and Implementation - PLDI '14)

DroidForce: Enforcing Complex, Data-Centric, System-Wide Policies in Android - Arzt, Steven; Rasthofer, Siegfried; Lovat, Enrico; Bodden, Eric (International Conference on Availability, Reliability and Security (ARES 2014))

Kehrtwende in der Gesundheitspolitik - Unnötige Abkehr von einer erfolgreichen Reform zur Finanzierung der gesetzlichen Krankenversicherung - Schmitz, Hendrik; Augurzky, B.; Roppel, U. (RWI Position)

The Challenge of Assessing the Market Value of Private Companies Using a Standardized Combination Method for Tax Purposes – Lessons to be Learned from Past Experience - Müller, Jens
When taxes on capital or wealth are levied, in most countries companies have to be assessed in terms of their market value (MV). Estimating the MV of private companies for tax purposes is a challenging task for tax authorities as MVs are not available. In this study, I empirically analyse to what extent an accounting-based tax valuation method for private companies, a simplified residual income model, succeeds in matching the MV. I refer to the mandatory Standardised Combination Model that is a special case of methods commonly used in several countries. In the absence of market prices for private companies, I use a sample of small German public companies as a proxy. I validate this approach using a sensitivity analysis that involves matching the sample of public companies with that of private companies. The results imply that the mandatory Standardised Combination Model leads to a severe unequal treatment not only between public and private companies but also among private companies across and within industries. Furthermore, I simulate the effects of variation in the key parameters and highlight their impact on the approximation quality of the Standardised Combination Method. The findings are relevant to tax reform discussions as well as to tax policy-makers and practitioners in many countries.

The Role of prior Entrepreneurial Exposure in the Entrepreneurial Process: A Review and Future Research Implications. - Zapkau, F B; Schwens, C; Kabst, Rüdiger (Journal of Small Business Management.)

Social media and e-participation: Challenges of social media for managing public projects. - Vogt, S; Förster, B; Kabst, Rüdiger (International Journal of Public Administration in the Digital Age.)

Foreign Direct Investments and domestic employment of German SMEs: The moderating effect of owner-management. - Zapkau, F B; Schwens, C; Kabst, Rüdiger (Journal of Small Business Management (JSBM).)

Linking Transaction Cost and Social Exchange Theory to Explain Strategic Alliance Performance: A Meta-Analytic Structural Equation Model. - Isidor, R; Steinmetz, Holger; Schwens, C; Kabst, Rüdiger (International Journal of Strategic Business Alliances.)

Configurations of e-HRM - An Empirical Exploration. - Strohmeier, S; Kabst, Rüdiger (Employee Relations.)

A Fuzzy Security Investment Decision Support Model for Highly Distributed Systems - Yasasin, Emrah; Rauchecker, Gerhard; Prester, Julian; Schryen, Guido (1st Workshop on Security in highly connected IT systems (SHCIS 14))

Emergency Response in Natural Disaster Management: Allocation and Scheduling of Rescue Units - Wex, Felix; Schryen, Guido; Feuerriegel, Stefan; Neumann, Dirk (European Journal of Operational Research)

Risk Reduction in Natural Disaster Management Through Information Systems: A Literature review and an IS design science research agenda - Schryen, Guido; Wex, Felix (International Journal of Information Systems for Crisis Response and Management (IJISCRAM))
Natural disasters, including earthquakes, Tsunamis, floods, hurricanes, and volcanic eruptions, have caused tremendous harm and continue to threaten millions of humans and various infrastructure capabilities each year. In their efforts to take countermeasures against the threats posed by future natural disasters, the United Nations formulated the ?Hyogo Framework for Action?, which aims at assessing and reducing risk. This framework and a global review of disaster reduction initiatives of the United Nations acknowledge the need for information systems research contributions in addressing major challenges of natural disaster management. In this paper, we provide a review of the literature with regard to how information systems research has addressed risk assessment and reduction in natural disaster management. Based on the review we identify research gaps that are centered around the need for acquiring general knowledge on how to design IS artifacts for risk assessment and reduction. In order to close these gaps in further research, we develop a research agenda that follows the IS design science paradigm.
Keywords: Natural Disaster Management; Risk Reduction; Hyogo Framework; IS Design Science; Literature review

Duality in fuzzy linear programming: A survey - Schryen, Guido; Hristova, Diana (OR -Spectrum)

Writing qualitative IS literature reviews ? Guidelines for synthesis, interpretation and guidance of research - Schryen, Guido (Communications of the AIS)

Methoden zur Zeit-Frequenz-Analyse bei der Untersuchung dispersionsbehafteter Signale - Bause, Fabian; Rautenberg, Jens; Feldmann, Nadine; Claes, Leander; Henning, Bernd

Rekonstruktion der räumlichen Schallwechseldruckverteilung unter Berücksichtigung der Orthogonalität optischer und akustischer Achsen beim Schlierenverfahren - Olfert, Sergei; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2014)

Lernverläufe sichtbar machen - Nur: Wie?! Eine Einführung in die Lernverlaufsdiagnostik mittels curriculumbasiertem Messens - Scheer, David (Sonderpädagogik in Rheinland-Pfalz)

(En-)Gendering a Popular Theatrical Genre. The Roles of Women in Nineteenth-Century British Melodrama - Tönnies, Merle

A combinatorial approach to the separation problem for regular languages. (Une approche combinatoire du problème de séparation pour les langages réguliers) - van Rooijen, Lorijn

On Separation by Locally Testable and Locally Threshold Testable Languages - Place, Thomas; van Rooijen, Lorijn; Zeitoun, Marc (Logical Methods in Computer Science)

Use Your Best Device! Enabling Device Changes at Runtime - Bokermann, Dennis; Gerth, Christian; Engels, Gregor (12th International Conference on Business Process Management (BPM 2014))

Anti-hegemoniale Strategien des Kleinen. Britische dokumentarische Farbfotografie als Kritik des Thatcherismus - Tönnies, Merle (Kulturen des Kleinen. Mikroformate in Literatur, Kunst und Medien)

Integration of offshore wind energy into the grid system in Germany: Modelling of a market oriented energy provision - Bouyraaman, Yassin; Bendfeld, Jörg; Krauter, Stefan (14th IAEE European Energy Conference- Sustainable Energy Policy and Strategies in Europe, Rome, Italy, October 28-31, 2014)

Integration of wind energy in power systems: Modeling of a market-orientated energy concept - Bouyraaman, Yassin; Bendfeld, Jörg; Krauter, Stefan; Breymann, P. (Proceedings of the World Renewable Energy Congress WREC XIII, London (UK), August 3-8, 2014)

Reduction of Offshore Wind farm power Feed-in ﬂuctuations via Power to Gas Storage Systems - Bouyraaman, Yassin; Bendfeld, Jörg (Solar 2014/Intersolar North America, San Francisco, July 6-10, 2014)

Advanced offshore Measurements for Windfarms - Bendfeld, Jörg; Balluff, Stefan (Solar 2014/Intersolar North America, San Francisco, July 6-10, 2014)

Solar Electric Power Systems. Second Edition - Krauter, Stefan

Measures to match load proﬁle with actual PV generation to achieve an effective integration into the energy system - Krauter, Stefan (Proceedings of the 6th World Conference of Photovoltaic Energy Conversion WCPEC 6, Kyoto (Japan), November 23-27, 2014)

Identiﬁcation and elimination of potential induced degradation (PID) at photovoltaic power plants - Krauter, Stefan (Proceedings of the 6th World Conference of Photovoltaic Energy Conversion WCPEC 6, Kyoto (Japan), November 23-27, 2014)

Performance and Yield Comparison of seven different Micro-Inverters. - Krauter, Stefan; Bendfeld, Jörg; Gohardehi, A.; Sadati, A. (Proceedings of the 6th World Conference of Photovoltaic Energy Conversion WCPEC 6, Kyoto (Japan), November 23-27, 2014)

Micro combined heat and power plants (micro-CHP) in combination with photovoltaics for autonomous local power and heat supply. - Krauter, Stefan; Bouyraaman, Yassin; Bendfeld, Jörg; Japs, Ewald (Proceedings of the 6th World Conference of Photovoltaic Energy Conversion WCPEC 6, Kyoto (Japan), November 23-27, 2014)

Photovoltaics and the Energy System: Adaptation of layout and load - Krauter, Stefan (Proceedings of the World Renewable Energy Congress WREC XIII, London (UK), August 3-8, 2014)

An Optimized Load Frequency Control of a De-centralized Energy System Using Plug-in Electric Vehicles - Ameli, Ali; Ameli, H.; Krauter, Stefan; Hanitsch, Rolf (Proceedings of the MES-BREG 2014 Symposium “Innovating Energy Access for Remote Areas: Discovering untapped resources”, UC Berkeley (USA), April 10-12, 2014)

Energy-economic comparison of photovoltaic modules equipped with a layer of conventional and improved phase-change material - Japs, Ewald; Peters, S.; Sonnenrein, Gerrit; Krauter, Stefan (Proceedings of the 40th IEEE Photovoltaic Specialists Conference, Denver (USA), June 8-13, 2014)

Integration of PV into the Energy System: Challenges and Measures for Generation and Load Management - Krauter, Stefan; Japs, Ewald (Proceedings of the 40th IEEE Photovoltaic Specialists Conference, Denver (USA), June 8-13, 2014)

Plant layout modiﬁcations and load adaptation to integrate Photovoltaics in the energy system. - Krauter, Stefan (Proceedings of the 29th European Photovoltaic Solar Energy Conference and Exhibition, Amsterdam (The Netherlands), September 22-16, 2014)

Integration Erneuerbarer Energien: Herausforderungen und Maßnahmen im Erzeugungssektor und Lastmanagement - Krauter, Stefan (uwf Umwelt Wirtschafts Forum)

Feasibility of Base Station Coordination and Dynamic Backhaul Network Configuration in Backhaul Networks with Limited Capacity - Dräxler, Martin; Karl, Holger (Proceedings of 20th European Wireless Conference)

Analytic quantification of outage probability and radiated power of cooperative base stations - Herlich, Matthias; Karl, Holger (12th International Symposium on Modeling and Optimization in Mobile, Ad Hoc, and Wireless Networks (WiOpt) 2014)

The Paradigm of Self-optimization - Dellnitz, Michael; Dumitrescu, Roman; Flaßkamp, Kathrin; Gausemeier, Jürgen; Hartmann, Philip; Iwanek, Peter; Korf, Sebastian; Krüger, Martin; Ober-Blöbaum, Sina; Porrmann, Mario; Priesterjahn, Claudia; Stahl, Katharina; et al. (Lecture Notes in Mechanical Engineering)

Optimal control of a switched reluctance drive by a direct method using a discrete variational principle - Flasskamp, Kathrin; Ober-Blobaum, Sina; Schneider, Tobias; Bocker, Joachim (52nd IEEE Conference on Decision and Control)

Control strategies on stable manifolds for energy-efficient swing-ups of double pendula - Flaßkamp, Kathrin; Timmermann, Julia; Ober-Blöbaum, Sina; Trächtler, Ansgar (International Journal of Control)

Methods for the Design and Development - Anacker, Harald; Dellnitz, Michael; Flaßkamp, Kathrin; Groesbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Horenkamp, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Korf, Sebastian; Krüger, Martin; Müller, Wolfgang; et al. (Lecture Notes in Mechanical Engineering)

Optimierte 3D Morphologiedarstellung tomographischer Datensätze des Herzens - Arens, S.; Domik, Gitta; Weise, R.; Holzinger, J.; Burchert, W.

Das Praktikum – Rechte und Pflichten eines arbeitsrechtlichen Rechtsverhältnisses - Krimphove, Dieter (Betriebs-Berater)

Neues zur Geltung nicht umgesetzter europäischer Richtlinien - Krimphove, Dieter (EuZW)

Rechtsfragen der Rekrutierung ausländischen Personals - Krimphove, Dieter; Lüke, Christoph (Betriebs-Berater)

Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013

Symmetry-Selective Third-Harmonic Generation from Plasmonic Metacrystals - Chen, Shumei; Li, Guixin; Zeuner, Franziska; Wong, Wing Han; Pun, Edwin Yue Bun; Zentgraf, Thomas; Cheah, Kok Wai; Zhang, Shuang (Physical Review Letters)

Hochauflösende Holografie - Zentgraf, Thomas (Physik in unserer Zeit)